Reception Histories : Rhetoric, Pragmatism, and American Cultural Politics - Mailloux, Steven (Book collections on Project MUSE., 1998)
In his earlier Rhetorical Power, Steven Mailloux presented an innovative and challenging strategy for combining critical theory and cultural studies. That book has stimulated wide-ranging discussion and debate among diverse audiences-students and specialists in American studies, speech communications, rhetoric/composition, law, education, biblical studies, and especially literary theory and cultural criticism. Reception Histories marks a further development of Mailloux's influential critical project, as he demonstrates how rhetorical hermeneutics uses rhetoric to practice theory by doing history. Reception Histories works out in detail what rhetorical hermeneutics means in terms of poststructuralist theory (Part One), nineteenth-century U.S. cultural studies (Part Two), and the contemporary history of curricular reform within the so-called Culture Wars (Part Three). Mailloux situates, defends, and elaborates the theory he first proposed in Rhetorical Power, and he exemplifies it with a new series of provocative reception histories. He also both critiques and reconceptualizes the version of reader response criticism he developed in his first book, Interpretive Conventions. Throughout Reception Histories, Mailloux demonstrates his distinctive blend of neopragmatism and cultural rhetoric study. By tracing the rhetorical paths of thought, this book offers a new way to read the current volatile debates over higher education and contributes its own original proposals for shaping the future of the humanities.